PERBEDAAN HASIL BELAJAR MATEMATIKA ANTARA MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DENGAN TWO STAY TWO STRAY (TSTS) BERDASARKAN SELF-EFFICACY SISWA SMP NEGERI I AMPANA KOTA - Nismawati, Nismawati; Ismaimuza, Dasa; Idris, Mustamin (AKSIOMA : Jurnal Pendidikan Matematika, 2016)
Abstract:The research aimed to describe the difference between studentsâ learning outcomes in mathematics who were given STAD cooperative learning model and those who were given TSTS Cooperative Learning Model based on studentsâ self-efficacy. This research was conducted in SMPN 1 Ampana City by using quasi-experimental method with 2 x 3 factorial design. The cooperative learning model is divided into two factors, namely Teams Achievement Division (STAD) cooperative learning model and Two Stay Two Stray (TSTS) cooperative learning model. The instrument used was self-efficacy questionnaire and the result of mathematics test. The data analysis used was two-way anava test analysis and t-scheffe test. Some of the research findings reveal that (1) there is the difference between mathematics learning outcomes of students given STAD model and those who were given TSTS model, (2) there is the difference between mathematics learning outcomes of students having self-efficacy (high, medium, and low), (3) there is any interaction between cooperative learning model and self-efficacy on studentsâ learning outcomes.KeyWords: STAD Cooperative Learning Model, TSTS Cooperative Learning Model, Self-efficacy, Studentsâ Learning Outcomes